(untitled) (Journal of University of Babylon for Engineering Sciences, 2025)
This work aims to improve the mechanical characteristics of recycled aggregate self-compacting concrete (SCC) mixtures by immersing recycled aggregate (RA) in a cement silica fume slurry (CSFS). An experimental study was conducted on several mixtures made up of a variety of aggregate type (normal aggregate, untreated recycled aggregate, treated recycled aggregate) utilizing different replacement ratios of 0%, 30%, 60%, and 100% of recycled aggregate. All mixes were tested for their fresh characteristics using slump flow, T500, and V-funnel tests, and their hardened characteristics were measured by compressive, splitting, and flexural concrete strength. The results indicated that the suggested treatment approach was effective for the physical characteristics of treated recycled aggregate, which exhibited greater specific gravity and reduced water absorption compared to untreated recycled aggregate. Regarding the fresh properties, research results indicated that most of the untreated RA-SCC mixtures met the Self-Compacting Concrete criteria (EFNARC guidelines), influencing the stated slump flow diameter of 600–685 mm, T500 ranging from 2.2–3.8 seconds, and V-funnel flow time between 5.1–13.7 seconds. For hardened characteristics, it was observed that replacing natural aggregate (NA) with recycled aggregate (RA) resulted in a significant reduction in compressive and tensile concrete strength values. In contrast, SCC mixtures, including treated RA, exhibited enhanced compressive, splitting tensile, and flexural strengths proportional to the replacement percentage. Thus, the results indicated that it is possible to produce SCC mixtures using treated recycled aggregates that offer reliable structural performance when utilized in reinforced elements. Finally, the effects of untreated RA, treated RA, and replacement ratio on the mechanical properties of the SCC mixes were individually quantified by the power equations, and a model for predicting the splitting and flexural strength of sustainable concrete mixes was proposed and verified.